Immunogenicity and protective efficacy of a multi-antigenic adenovirus-based vaccine candidate against Mycobacterium tuberculosis - Yun, Jin-Seung; Shin, Eunkyung; Lee, Young-Ran; Lee, Jung-Ah; Lee, Hyeokjin; Kim, Jong-Seok; Shin, Sung Jae; Ha, Sang-Jun; Lee, Sang-Won; Kim, Dokeun; Yoo, Jung-Sik; Jeong, Hye-Sook (Frontiers in Microbiology, 2025)
IntroductionThe inadequate efficacy of the Bacillus Calmette–Guérin (BCG) vaccine against adult pulmonary tuberculosis (TB) necessitates the development of new and effective vaccines. Human adenovirus serotype 5 (Ad5), which induces T-cell response, is a widely used viral vector. In this study, we aimed to evaluate the efficacy of a multi-antigenic recombinant Ad5 vectored vaccine and determine the optimal immunization route for enhanced immune response against Mycobacterium tuberculosis.MethodsWe constructed a multi-antigenic recombinant Ad5 vectored vaccine expressing four antigens (Ag85B-ESAT6-MPT64-Rv2660c) of M. tuberculosis (rAd-TB4), immunized with rAd-TB4 (5 × 107 infectious virus units/mouse) twice at an interval of 4 weeks starting at 10 weeks after BCG priming, and evaluated its boosting efficacy in a BCG-primed mouse model, and determined the optimal immunization route.ResultsCompared with the BCG-only (2 × 105 colony forming units/mouse), subcutaneous injection of rAd-TB4 (1 × 107 infectious virus units/mL; two doses) elicited a T-cell response and cytokine production in lung lymphocytes and splenocytes. rAd-TB4 immunization significantly reduced bacterial loads and inflamed lung areas compared to BCG immunization (p < 0.01) and protected against the H37Rv challenge performed at 17 weeks of BCG priming. RNA sequencing of the whole blood of rAd-TB4-vaccinated mice collected pre- and, 1 and 4 weeks post-infection, identified differentially expressed genes associated with immune and inflammatory responses, especially those in the Wnt signaling pathway.ConclusionOur results indicate that rAd-TB4 immunization enhances the immune response to the vaccine boosting antigens in BCG-primed mice, making it a potential adult pulmonary TB vaccine candidate.